My many colored days - Seuss, Dr Dr.; Johnson, Steve, 1960-; Fancher, Lou (New York : Alfred A. Knopf : Distributed by Random House, 1996)
This rhyming story describes each day in terms of a particular color which in turn is associated with specific emotions. (Gr. PreK-2)
AD 190
Adult 190
Keywords: Color -- Fiction; Day -- Fiction; Emotions -- Fiction; Stories in rhyme